Self-replicating recombinant virus-like particles of lentivirus proliferating in glioblastoma cells and normal human macrophages - Herman D. Moshkoff; Andrey E. Moshkoff; Dmitry A. Moshkoff (Журнал микробиологии, эпидемиологии и иммунобиологии)
Introduction. Both attenuated and inactivated vaccines are used in disease control. Inactivated vaccines are very diverse and include whole cell and acellular vaccines containing protein target antigens or nucleic acids encoding target antigens. Immunity induced by inactivated vaccines is not believed to be long-lasting. It is very problematic to develop a vaccine against viruses that integrate into the genome of the host cell, as well as against persistent viruses that penetrate the central nervous system (CNS), which is typical for the human immunodeficiency virus type 1 (HIV-1).